Pattern recognition : 8th Mexican Conference, MCPR 2016, Guanajuato, Mexico, June 22-25, 2016, Proceedings /: 8th Mexican Conference, MCPR 2016, Guanajuato, Mexico, June 22-25, 2016, Proceedings. (2016) - Unknown
No abstract available